2016
DOI: 10.1159/000443823
|View full text |Cite
|
Sign up to set email alerts
|

Sedation during Minimal Invasive Surfactant Therapy in Preterm Infants

Abstract: Background: There is no data available whether sedation should be given during minimally invasive surfactant therapy (MIST). Objective: To compare the level of comfort of preterm infants receiving sedation versus no sedation for MIST. Methods: A retrospective study of preterm infants receiving MIST was performed in Leiden University Medical Center in 2014. Sedation (propofol 1 mg/kg) was optional and left to the discretion of the caregiver. Standardized COMFORTneo scores were compared, and COMFORTneo <14 was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 24 publications
2
100
0
Order By: Relevance
“…It is difficult to comment from the available data whether the use of premedication would help reduce the incidence of bradycardia and/or desaturation episodes during the LISA procedure, as noted in some studies 31 32. A recent cohort control study showed better comfort scores with the use of sedation but a greater risk of intubation during or within 24 hours after the procedure 40. Future studies could determine the benefits and the risks associated with the use of sedation during the LISA procedure.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to comment from the available data whether the use of premedication would help reduce the incidence of bradycardia and/or desaturation episodes during the LISA procedure, as noted in some studies 31 32. A recent cohort control study showed better comfort scores with the use of sedation but a greater risk of intubation during or within 24 hours after the procedure 40. Future studies could determine the benefits and the risks associated with the use of sedation during the LISA procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinicians prefer to use a combination of a short-acting opiate, muscle relaxant and atropine to maximize comfort and improve the chances of successful intubation [164]. However, there is a balance between ensuring comfort during laryngoscopy and not oversedating infants when trying to maintain them on non-invasive respiratory support [165]. Once stable on ventilation there is usually no need for routine sedation [166].…”
Section: Managing Blood Pressure and Perfusionmentioning
confidence: 99%
“…International guidelines recommend sedation for intubation but it can hamper spontaneous breathing, which is necessary for LISA. Recently, a study compared two groups undergoing LISA with or without sedation: the sedated newborns were more comfortable but needed ventilation more often 3. We report a retrospective analysis of 35 preterm infants who were sedated with propofol for LISA.…”
mentioning
confidence: 99%